Contributions of the NICHD neonatal research network's generic database to documenting and advancing the outcomes of extremely preterm infants - Bell, Edward F.; Stoll, Barbara J.; Hansen, Nellie I.; Wyckoff, Myra H.; Walsh, Michele C.; Sánchez, Pablo J.; Rysavy, Matthew A.; Gabrio, Jenna H.; Archer, Stephanie W.; Das, Abhik; Higgins, Rosemary D. (Seminars in perinatology, 2022)
The Eunice Kennedy Shriver National Institute of Child Health and Human Development Neonatal Research Network (NRN) maintains a database of extremely preterm infants known as the Generic Database (GDB). Begun in 1987, this database now includes more than 91,000 infants, most of whom are extremely preterm (<29 weeks gestation). The GDB has been the backbone of the NRN, providing high quality, prospectively collected data to study the changing epidemiology of extreme prematurity and its outcomes over time. In addition, GDB data have been used to generate hypotheses for prospective studies and to develop new clinical trials by providing information about the numbers and characteristics of available subjects and the expected event rates for conditions and complications to be studied. Since its inception, the GDB has been the basis of more than 200 publications in peer-reviewed journals, many of which have had a significant impact on the field of neonatology.